Early and late pulmonary manifestations of COVID-19 on computed tomography scan - Kaabi, Samarra Mongi; Madkhali, Ahmad Nasser; Alqahtani, Naif Hussain; Bakhsh, Ammar Adel; Alharthi, Yousef Hussain; Alwadai, Nawal Misfer; Alotaibi, Abdullah Meshaan; Alotaibi, Saad Obaid; Aljohani, Ahmed Abdualrhman; Aldarsouny, Sarah Thamer; Ahmad, Doha Jamal (International Journal Of Community Medicine And Public Health, 2021)
Computed tomography (CT) of the chest has been previously reported as an efficacious approach for the early diagnosis and suspicion of COVID-19 infection, as diagnosis with other modalities is usually time-consuming and cannot detect the disease within the early stages. Many pulmonary manifestations have been previously observed under CT imaging of the chest. All of them have been linked with the different stages of the disease, indicating their abilities to diagnose and follow-up these patients.This present literature review aims to discuss the role of CT imaging of the chest in COVID-19 infections and it also aims to elaborate the common pulmonary manifestations that can be frequently observed to help with the diagnosis and prognosis of the disease. Moreover, ground-glass opacities (GGOs) have been reported among studies in the literature to be the most common findings as they remain the earliest among other diseases. The literature review also aims to invistagate whether GGOs can fade away or progress to consolidate in order to decide the prognosis of the disease and to identify the severity of cases. Consolidations have also been previously stated among studies in the literature as frequent pulmonary manifestations affecting patients with COVID-19 infections and are estimated to be present in 2-63% of patients with COVID-19 infections. Other pulmonary manifestations might also include bronchiectasis, lymphadenopathy, nodules, pleural effusion or thickening, and halo sign.